2014
DOI: 10.1002/2014rg000464
|View full text |Cite
|
Sign up to set email alerts
|

Future changes to the intensity and frequency of short-duration extreme rainfall

Abstract: Evidence that extreme rainfall intensity is increasing at the global scale has strengthened considerably in recent years. Research now indicates that the greatest increases are likely to occur in short-duration storms lasting less than a day, potentially leading to an increase in the magnitude and frequency of flash floods. This review examines the evidence for subdaily extreme rainfall intensification due to anthropogenic climate change and describes our current physical understanding of the association betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

44
900
2
7

Year Published

2015
2015
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 1,122 publications
(953 citation statements)
references
References 244 publications
(356 reference statements)
44
900
2
7
Order By: Relevance
“…This long-term process has resulted in the alteration of the natural hydrological cycle by reducing the infiltration and evaporation capacity of urban catchments, increasing surface runoff, and reducing groundwater recharge. While some studies highlighted a decrease of recharge as a result of an increase of impervious was also confirmed in other studies (e.g., Westra et al, 2014). This will be accompanied by a more frequent occurrence of flooding events in urban areas (Carbone et al, 2015b).…”
Section: Introductionsupporting
confidence: 60%
“…This long-term process has resulted in the alteration of the natural hydrological cycle by reducing the infiltration and evaporation capacity of urban catchments, increasing surface runoff, and reducing groundwater recharge. While some studies highlighted a decrease of recharge as a result of an increase of impervious was also confirmed in other studies (e.g., Westra et al, 2014). This will be accompanied by a more frequent occurrence of flooding events in urban areas (Carbone et al, 2015b).…”
Section: Introductionsupporting
confidence: 60%
“…Trenberth et al 2003), or rather a super-CCrate (Lenderink and van Meijgaard 2008;Berg et al 2013;Westra et al 2014). When comparing historical to end of century projections in the RCP8.5 scenario, Ban et al (2015) found an intensification of the extremes according to the standard CC-rate over the Alps and surrounding regions, while for the southern UK, Kendon et al (2014) found that the increase in convective precipitation was consistent with a super-CC-rate.…”
Section: Atmospheric Conditions Leading To Convective Precipitationmentioning
confidence: 97%
“…The CC relation considerably influences the changes in the extreme precipitation intensity under warmer climates (Betts and Harshvardhan 1987;Trenberth et al 2003;Held and Soden 2006;Pall et al 2007;Kharin et al 2007; O' Gorman and Muller 2010;Muller et al 2011;Romps 2011;Westra et al 2014). Considering this, observed relations between extreme precipitation and temperature have received considerable attention.…”
Section: Introductionmentioning
confidence: 99%